Validation of the internal structure of the Warr, Cox and Wall Job Satisfaction questionnaire using the Free Scale Least Squares estimation method - Ucedo Silva, Víctor (2021)
The objective of the research was to evaluate the validity of the internal structure and the reliability of the “Warr, Cox and Wall Job Satisfaction" questionnaire to be applied to higher education teachers. Method: Using of the Confirmatory Factor Analysis with the method of estimation of Least Squares of Free Scale in unifactorial and bifactorial measurement models, in a sample of 242 higher education teachers. Results: Obtaining the indicators Chi of 59.024 and 63.185, GFI of 0.984 and 0.983, AGFI of 0.978 and 0.977, RMSR of 0.066 and 0.070, respectively, being within the appropriate parameters. The degree of reliability was evaluated with Cronbach's Alpha coefficient=0.867 with a CI(99 %)[0.832; 0.897], the composite reliability coefficient in the unifactorial model ω = 0.908 and in the bifactorial model ω = 0.913, being the internal consistency of the scale very better. Concluding that the internal structure of the job satisfaction scale is valid and reliable.